Alternative trans-parenchymal access for percutaneous contact nephrolithotripsy - Yu. Yu. Malinin (Вестник урологии)
Introduction. An actual issue of modern endoscopic surgery for urolithiasis is the development of techniques for optimal access to the stone. Percutaneous access during contact nephrolithotripsy (PCNL) is believed to reach the pyelocalyceal system (PCS) along the shortest trajectory and pass through the small calyces. It assumes multi-accessibility, as well as interventional cascading. Anatomically, the kidney is divided into five relatively independent segments in terms of blood supply. The thickness of the posterior one is only a quarter of the thickness of the kidney, which allows us to assume a significantly smaller number of vessels in this segment even outside the Zondek (Brödel) bloodless line.Purpose of the study.To prove the possibility of using an optimized transparenchymal approach in PCNL based on the renal vascular structure.Material and methods. A prospective analysis of the treatment of 41 patients with urolithiasis who hadPCNL. Before surgery, patients were randomized by gender, age, average stone size, and urolithiasis forms. Subjects were divided into two groups. Group 1 (study) —20 (48.8%) patients underwent PCNL through trans-parenchymal access to the inferior-lateral parts of the pelvis or the large lower renal calyx due to the ventral orientation of the lower small calyces. Group 2 (control) — 21 (51.2%) patients underwent standard PCNL. The creation of access to PCS was provided simultaneously with Doppler ultrasound of the renal vessels to prevent damage to the segmental and interlobular vessels of the kidney.Results. In 73.2% of patients, the blood supply in the region of standard access to the PCS goes through the posterior segmental artery, which does not supply blood to the lower half of the kidney (type 1 blood supply). In 26.8% of patients, branches of the posterior segmental artery cross the projection of the inferior calyces (type 2 blood supply). In cases where it is impossible to perform a standard puncture of the PCL (patients of the first group), type 1 blood supply allows you to safely make an alternative trans-parenchymal access directly to the lower calyx or pelvis through the inferior-lateral dorsal wall. The optimization of the access decreasesthe average operation time by 1.4 times and the average number of accesses by 1.3 times.Conclusion. Doppler ultrasound scanning allows to visualize of arterial vessels, which helps to provide safe trans-cutaneous puncture access to PCS. In 73.2% of patients, the region of the posterior surface of the pelvis and the lower calyx was identified with the possibility of an anatomically justified low-traumatic trans-parenchymal access. It significantly expands the area of the parts of the PCS accessible for direct intervention. The creation of a trans-parenchymal access to the lower lateral parts of the renal pelvis allows reducing the total number of accesses to the PCS, which reduces the operation time and the number of complications.